2020
DOI: 10.1002/anie.202002391
|View full text |Cite
|
Sign up to set email alerts
|

An Activatable Lanthanide Luminescent Probe for Time‐Gated Detection of Nitroreductase in Live Bacteria

Abstract: Herein we report the development of a turn‐on lanthanide luminescent probe for time‐gated detection of nitroreductases (NTRs) in live bacteria. The probe is activated through NTR‐induced formation of the sensitizing carbostyril antenna and resulting energy transfer to the lanthanide center. This novel NTR‐responsive trigger is virtually non‐fluorescent in its inactivated form and features a large signal increase upon activation. We show that the probe is capable of selectively sensing NTR in lysates as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 35 publications
(15 reference statements)
2
39
0
Order By: Relevance
“…Thus, a continuous increase of the fluorescence intensity was observed with increasing pH and temperature up to pH 7 and 37 °C, whereas at larger values the fluorescence intensity started to decrease. The effect of the temperature on the reaction of 1b with nitroreductase is in good agreement with the reported activities of the enzyme towards nitroarene derivatives [9][10][11]15 but the optimal pH value lies usually slightly higher at pH 7.4. [9][10][11]15 The lower fluorescence intensity at higher pH values is presumably caused by a slow degradation of the substrate by nucleophilic addition of the hydroxide ion to the benzo[b]quinolizinium at C6 position and subsequent ring opening reaction, as usually observed for this class of compounds.…”
Section: 5supporting
confidence: 89%
See 2 more Smart Citations
“…Thus, a continuous increase of the fluorescence intensity was observed with increasing pH and temperature up to pH 7 and 37 °C, whereas at larger values the fluorescence intensity started to decrease. The effect of the temperature on the reaction of 1b with nitroreductase is in good agreement with the reported activities of the enzyme towards nitroarene derivatives [9][10][11]15 but the optimal pH value lies usually slightly higher at pH 7.4. [9][10][11]15 The lower fluorescence intensity at higher pH values is presumably caused by a slow degradation of the substrate by nucleophilic addition of the hydroxide ion to the benzo[b]quinolizinium at C6 position and subsequent ring opening reaction, as usually observed for this class of compounds.…”
Section: 5supporting
confidence: 89%
“…The effect of the temperature on the reaction of 1b with nitroreductase is in good agreement with the reported activities of the enzyme towards nitroarene derivatives [9][10][11]15 but the optimal pH value lies usually slightly higher at pH 7.4. [9][10][11]15 The lower fluorescence intensity at higher pH values is presumably caused by a slow degradation of the substrate by nucleophilic addition of the hydroxide ion to the benzo[b]quinolizinium at C6 position and subsequent ring opening reaction, as usually observed for this class of compounds. 20 Furthermore, excitation spectra indicated that the new long-wavelength absorption maxima at 447 nm and 480 nm correspond to the newly formed emitting species (Figure 2, Figure S4A).…”
Section: 5supporting
confidence: 89%
See 1 more Smart Citation
“…In recent years, various enzyme-sensitive probes have been reported 117 . These probes use enzymes to specifically recognize the performance of a reaction substrate and have various design mechanisms for enzyme detection, including in-situ self-assembly, intramolecular cyclization, FRET, ICT, and group self-elimination.…”
Section: Design Mechanism Of Molecular Probes For Enzyme Detectionmentioning
confidence: 99%
“…Brennecke et al . published their NTR responsive lanthanide probe 21 [59] . The nitro group on this probe was reduced to its corresponding amine due to reducing action of NTR, thereby releasing iminoquinone methide.…”
Section: Small Molecule Based Ntr Probesmentioning
confidence: 99%